Czech Republic Report on the Observance of Standards and Codes?Fiscal Transparency Banking Supervision Insurance Regulation Securities Regulation Payment Systems and Monetary and Financial Policy Transparency Updates : Report on the Observance of Standards and Codes-Fiscal Transparency, Banking Supervision, Insurance Regulation, Securities Regulation, Payment Systems, and Monetary and Financial Policy Transparency-Updates. (IMF Staff Country Reports; Country Report ;, 2002)
This paper presents an update to the Czech Republic's Report on the Observance of Standards and Codes (ROSC) on Fiscal Transparency, Banking Supervision, Insurance Regulation, Securities Regulation, Payment Systems, and Monetary and Financial Policy Transparency. The Czech Republic continues to lack a comprehensive perspective on fiscal risks. Although the extension of government guarantees has dropped sharply, other forms of contingent liabilities are still not fully captured, for example, those resulting from the operations of the National Property Fund or the Czech Consolidation Agency. Moreover, there is no requirement to quantify tax expenditures.